Culturally Integrated Behavior-Centered Design Using a Visual–Auditory–Kinesthetic Approach to Prevent Stunting - Nurul Hidayah; Norliana Ekawati; Nur Ariska Ramadhana; Amelia Kartika (Poltekkes Kemenkes Palu, 2026)
Background: Stunting prevalence in South Kalimantan is 24.6%, exceeding the national average and indicating a persistent public health challenge. Despite various educational interventions, the stunting cases remain high. This study aimed to develop and evaluate a Behavior-Centered Design educational medium that integrates Banjar cultural values, Maasi (obedience), Maher (positive habituation), and Manuntung (commitment to completion), using a visual–auditory–kinesthetic learning approach to enhance adolescent engagement in stunting prevention. Methods: A level-3 Research and Development design with a controlled pretest-posttest method was applied to 76 adolescents equally assigned to intervention and control groups. The intervention consisted of four culturally contextualized educational games (comprehensive-card, factor-cards, shame-blocks, and true-false cards) each emphasizing anemia, nutrient balance, healthy behavior, and stunting prevention. Data were collected using a validated questionnaire assessing cognitive, attitude, and motivation toward stunting prevention. Results: Statistical analyses (paired t-tests, independent t-tests, ANOVA, post hoc) showed significant improvements in all domains (p < 0.05), cognitive increasing by 25.7%, attitude by 30.8%, and motivation by 17.1%. The games demonstrated strong cultural strong resonance, with representation of Maasi (97.36%), Maher (92.10%), and Manuntung (97.36%) values. Conclusion: In conclusion, the culturally integrated Behavior-Centered Design educational medium effectively enhances adolescent engagement and behavioral readiness for stunting prevention, offering a promising culturally grounded model for public health promotion in South Kalimantan.